Elevating Careers through Technology and Creativity: A Middle-Level Manager's Odyssey - Hummaira Jabeen; Rana Salman Anwar; Rizwan Ahmed Raheem (Journal of Management Practices, Humanities and Social Sciences, 2024)
Purpose: This research investigates the influence of Middle-level managers' AI/GPT tools and technological proficiency on workplace diversity exposure, career calling, career advancement aspirations, and inclusivity perception in NBEAC-accredited universities in Pakistan. Additionally, the study explores the mediating role of workplace creativity in these relationships. The study adopts a quantitative research design and employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 313 Middle-level managers, including Assistants, Program officers, Assistant Exam Controllers, and Assistant Registrars, through personal contacts and references. The data was collected in May and June for this research and the study utilizes established scales from previous research to measure the variables of interest. The results reveal that Middle-level managers' AI/GPT tools technological proficiency positively influences workplace diversity exposure, career calling, career advancement aspirations, and inclusivity perception. Workplace creativity significantly mediates the relationships between technological proficiency and workplace diversity exposure, career calling, and career advancement aspirations. Study contributes to the existing literature by examining the mediating role of workplace creativity and its influence on the relationships between technological proficiency and career-related perceptions among Middle level managers in the educational context of NBEAC accredited universities in Pakistan. However, this study used data of Pakistani nationals only, while future studies can conduct this research on other nations too.